Transforming anti-doping education with web-based interactive programs and applications: A scoping review - K.P. Bingham; L. Lazuras; V. Barkoukis; A.-M. Elbe; L. Moustakas; N. Ntoumanis (Emerging Trends in Drugs, Addictions, and Health)
Background: Doping has become a global social, moral and institutional challenge that has serious consequences for athletes and the integrity of sports. Since educational tools are deemed not to be sufficiently effective in minimizing doping, the benefits of digital and web-based (desktop and/or mobile) interventions are being explored. Objective: The present study undertakes a scoping review of research on web-based anti-doping interventions to provide an overview of peer-reviewed studies that have examined their effectiveness in raising awareness of doping among athletes and exercisers. Design: Online databases were used to identify nine papers that examine a web-based anti-doping intervention. The review maps out the key PICO (population, intervention, comparator, outcome) characteristics of each web-based program and their effectiveness in reducing the risk for engaging in doping use. Results: The scoping review reveals that only seven web-based anti-doping interventions have been tested worldwide and that four appear to have been successful. Three studies present a different view of web-based anti-doping interventions and indicate they may be partially effective. Conclusions: The review suggests that newly emerging web-based anti-doping interventions have shown some success in improving knowledge and awareness of doping, reducing favourable attitudes towards doping, and reducing doping susceptibility. The review paves the way for future projects and encourages researchers to utilise cutting-edge technologies to ensure interventions are innovative, impactful and contemporaneous.